Toward Becoming Good Relatives: Not-Dancing to Centre Indigenous Presence in the Dance Classroom - Roth, Sammy; Shaffer, Miya; Blu Wakpa, Tria (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2024)
This co-written article considers the possibilities and limitations that community-engaged, decolonial pedagogies hold for challenging normative, settler-capitalist goals in dance education. Current mainstream discussions in US higher education demonstrate concern with utility and career readiness, especially in arts and humanities disciplines. In the performance-based classroom, these ideas can lend themselves to expectations of physical training to “prepare” students for a dance career. We argue that the alternative learning goals of not-dancing, listening to class attendees and collaborators, and working-for California tribal community partners can instead enable students and faculty to recognize and challenge implicit settler-capitalist frameworks and legacies of non-Native appropriation in undergraduate dance classes. We analyze a community-engaged, undergraduate seminar, titled Dance and Decolonization, which was taught by Tria Blu Wakpa, an Assistant Professor, with the assistance of her graduate student researchers, Sammy Roth and Miya Shaffer. This course asked students to support the cultural revitalization initiatives of individuals and representatives from three California Native tribes, which included archival research and dance revitalization efforts. We write this article as a conversation, following the pedagogical models offered by community partners who engaged students in dialogue, rather than teaching dances. We show how the course re-animated the space of the classroom to foreground Indigenous presence — an action which enabled students and faculty to identify and challenge historical and contemporary settler-capitalist power relations and, subsequently, recognize the constraints of learning about Indigenous issues in a land grant institution. In discussing the course, we offer strategies to work towards becoming "good relatives" from different community outsider positionalities: by not-dancing, listening, and working-for, we can be present to Indigenous presence and aim to be in relation with Indigenous peoples and land.